2018
DOI: 10.1007/s00234-018-2034-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute invasive fungal rhinosinusitis: MR imaging features and their impact on prognosis

Abstract: AIFRS showed frequent extra-sinonasal involvement and variable MR enhancement patterns. An enhancement pattern of LoCE was seen in about half of the cases and was a unique prognostic factor among the various clinico-radiologic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
6
41
0
6
Order By: Relevance
“…Common observations in our benign BT cases of thin rim enhancement around the nonenhancing areas (Figs 3 and 4) and intermediate and high signal intensity on the T2-weighted images were not consistently described in the cases of IFRS reported in the literature [1][2][3][4]7 or seen in our case of IFRS. Choi et al 4 stated that in patients with IFRS, "Although LoCE (Lack of Contrast Enhancement) showed variable signal intensity (SI), homogeneously or heterogeneously enhancing lesions showed exclusively low SI (100%, 12/12) on T2WI." Seo et al, 3 in their review of 23 patients with IFRS, found 17 patients who had nonenhancing areas in the sinonasal region (13 with extension into adjacent structures), and the signal intensity on the T2WI was variable, with most being hyperintense and many also having areas of iso-or hypointensity compared with the brain cortex.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Common observations in our benign BT cases of thin rim enhancement around the nonenhancing areas (Figs 3 and 4) and intermediate and high signal intensity on the T2-weighted images were not consistently described in the cases of IFRS reported in the literature [1][2][3][4]7 or seen in our case of IFRS. Choi et al 4 stated that in patients with IFRS, "Although LoCE (Lack of Contrast Enhancement) showed variable signal intensity (SI), homogeneously or heterogeneously enhancing lesions showed exclusively low SI (100%, 12/12) on T2WI." Seo et al, 3 in their review of 23 patients with IFRS, found 17 patients who had nonenhancing areas in the sinonasal region (13 with extension into adjacent structures), and the signal intensity on the T2WI was variable, with most being hyperintense and many also having areas of iso-or hypointensity compared with the brain cortex.…”
Section: Discussionsupporting
confidence: 44%
“…Diffusion-weighted imaging may have little utility and is only mentioned by the authors of several series in the literature, and not necessarily with respect to the nasal turbinates. 2,4 Safder et al 2 described restricted diffusion in 2 cases; however, Choi et al 4 described facilitated diffusion in 2 of their cases. Choi et al also felt that the NE areas were due to coagulation necrosis rather than infarction, therefore explaining this imaging finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En un estudio que evaluó las características de la RM en pacientes con RSFIA, se constató que el compromiso extranasosinusal sería frecuente, afectando en 65% de los casos a la órbita 17 . La ausencia de realce con el contraste ocurriría en casi la mitad de los pacientes 17 , lo que podría ser explicado por la naturaleza angioinvasiva de la infección fúngica 12 . Este patrón de comportamiento al contraste además se asoció significativamente a mayor mortalidad, en comparación con los patrones homogéneo y heterogéneo 17 .…”
Section: Imagenologíaunclassified
“…La ausencia de realce con el contraste ocurriría en casi la mitad de los pacientes 17 , lo que podría ser explicado por la naturaleza angioinvasiva de la infección fúngica 12 . Este patrón de comportamiento al contraste además se asoció significativamente a mayor mortalidad, en comparación con los patrones homogéneo y heterogéneo 17 . En un estudio que evaluó las características tomográficas, se encontró que la presencia de erosión ósea, el engrosamiento de partes blandas, la extensión extrasinusal y el compromiso unilateral tienen un valor predictivo positivo (VPP) de 100%, mientras que los cambios inflamatorios mucoperiósticos de los senos paranasales tienen un valor predictivo negativo (VPN) de 100% 4 .…”
Section: Imagenologíaunclassified